ROLE OF INHIBITION OF CGMP-DEPENDENT PROTEIN KINASE (PKG) SIGNALLING ON ANTICONTRACTILE FUNCTION OF PERIVASCULAR ADIPOSE TISSUE. (April 2021) - Rosei, Claudia Agabiti; Rossini, Claudia; De Ciuceis, Carolina; Porteri, Enzo; Brami, Valeria; Nardin, Matteo; Chiarini, Giulia; Petelca, Alina; Coschignano, Maria Antonietta; Tiberio, Guido Alberto; Muiesan, Maria Lorenza; Rizzoni, Damiano
Abstract : Objective: Perivascular adipose tissue (PVAT) has an anticontractile effect.This capacity is lost in obesity (Circulation 2009) through adipocyte hypertrophy, leading to hypoxia, inflammation and oxidative stress. It has been previously demonstrated that cGMP-dependent protein kinase (PKG) plays a key role in regulating normal PVAT function (Cardiovasc Res. 2014). Aim of the study was to investigate functional responses of small resistance arteries with and without PVAT in normotensive subjects and obese patients, testing the effects of DT-2, (a peptidic highly selective inhibitor of PKG) on contractile response Figure. No caption available. Design and method: We have investigated 9 normotensive severely obese patients (Obese) and 6 hypertensive severely obese patients (Obese-Hyper) undergoing bariatric surgery, as well as 7 normotensive lean subjects (CTRL) undergoing an election surgical intervention.No sign of local or systemic inflammation was present in any subject or patient. Subcutaneous small resistance arteries were dissected and mounted on a wire myograph. A concentration-response curve to noradrenaline (NA, from 10–9 to 10–5Mol/l) was evaluated in vessels with intact prerivascular fat tissue (WF)and in vessels in which perivascular fat tissue was removed (NoF). Concentration response to NA was repeated in small arteries WF and NoF in the presence of DT-2 (125 nM) in both normoxic and hypoxic (95% N2/5%CO2 for 30')conditions Results: In normoxic conditions the presence of PVAT reduced contractile response to NA in small arteries from CTRL (ANOVA p = 0.04 vs. NoF). The anticontractile effect of PVAT completely disappeared in Obese and Obese-Hyper patients. In CTRL preincubation with DT-2 lead to increase contractile responses to NA in arteries WF (ANOVA p = 0, 04 WF+DT-2 vs WF). This effect was more evident during hypoxic conditions after incubation with DT-2 in all groups. No significant effect was observed on contractile response to NA in arteries WF and NoF from Obese and Obese-Hyper patients after incubation of DT-2, in normoxic conditions Conclusions: The anticontractile effect of PVAT is present in normotensive subjects and it is lost after inhibition of PKG signalling. The absence of effect after preincubation of DT-2 on arteries WF from Obese and Obese-Hyper patients suggests a dysregulation of PKG signalling pathways in these groups, which seems essential for its downstream dilator function in small resistance arteries